Dedication to A. A. Sommer, Jr - Joel Seligman (Washington University Law Quarterly, 2000)
All of the speakers we invited to the symposium are here today with one exception. Al Sommer’s health is not what it once was. Al is a figure who has had a commanding role in corporate and securities for the past four decades. After consultation with the Washington University Law Quarterly, I am honored to say that the Quarterly will be dedicating this symposium to Al.
Keywords: A. A. Sommer